No influence of ischemic preconditioning on running economy - Kaur, G.; Binger, M.; Evans, C.; Trachte, T.; Van Guilder, G. P. (European Journal of Applied Physiology, 2017)
Purpose: Many of the potential performance-enhancing properties of ischemic preconditioning suggest that the oxygen cost for a given endurance exercise workload will be reduced, thereby improving the economy of locomotion. The aim of this study was to identify whether ischemic preconditioning improves exercise economy in recreational runners. Methods: A randomized sham-controlled crossover study was employed in which 18 adults (age 27 ± 7 years; BMI 24.6 ± 3 kg/m2) completed two, incremental submaximal (65-85% VO2max) treadmill running protocols (3 × 5 min stages from 7.2-14.5 km/h) coupled with indirect calorimetry to assess running economy following ischemic preconditioning (3 × 5 min bilateral upper thigh ischemia) and sham control. Running economy was expressed as mlO2/kg/km and as the energy in kilocalories required to cover 1 km of horizontal distance (kcal/kg/km). Results: Ischemic preconditioning did not influence steady-state heart rate, oxygen consumption, minute ventilation, respiratory exchange ratio, energy expenditure, and blood lactate. Likewise, running economy was similar (P = 0.647) between the sham (from 201.6 ± 17.7 to 204.0 ± 16.1 mlO2/kg/km) and ischemic preconditioning trials (from 202.8 ± 16.2 to 203.1 ± 15.6 mlO2/kg/km). There was no influence (P = 0.21) of ischemic preconditioning on running economy expressed as the caloric unit cost (from 0.96 ± 0.12 to 1.01 ± 0.11 kcal/kg/km) compared with sham (from 1.00 ± 0.10 to 1.00 ± 0.08 kcal/kg/km). Conclusions: The properties of ischemic preconditioning thought to affect exercise performance at vigorous to severe exercise intensities, which generate more extensive physiological challenge, are ineffective at submaximal workloads and, therefore, do not change running economy.